2021
DOI: 10.1523/jneurosci.2771-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

A Heteromodal Word-Meaning Binding Site in the Visual Word Form Area under Top-Down Frontoparietal Control

Abstract: The integral capacity of human language together with semantic memory drives the linkage of words and their meaning, which theoretically is subject to cognitive control. However, it remains unknown whether, across different language modalities and input/output formats, there is a shared system in the human brain for word-meaning binding and how this system interacts with cognitive control. Here, we conducted a functional magnetic resonance imaging experiment based on a large cohort of subjects (50 females, 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 96 publications
1
12
1
Order By: Relevance
“…4). This observation converges with recent reports of a heteromodal semantic hub in the fusiform gyrus [66,67] to suggest that some integration might already occur in posterior temporal cortex, but additional studies are needed to clarify the functional implications of this finding.…”
Section: Discussionsupporting
confidence: 90%
“…4). This observation converges with recent reports of a heteromodal semantic hub in the fusiform gyrus [66,67] to suggest that some integration might already occur in posterior temporal cortex, but additional studies are needed to clarify the functional implications of this finding.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies suggested that predictive mechanisms are important in determining the RS, observed in the LFA for simple graphemes or letters (Grotheer & Kovács, 2014), in the superior temporal gyrus for word stress processing (Honbolygó et al, 2020) and in the superior temporal gyrus for lexical representations (Wang et al, 2021) as well as for semantic processes (Qin et al, 2021). These results combined with the Repetition probability effects for words 20 current study, in which the involvement of predictive processes is suggested for visual word recognition in the VWFA, suggest that top-down probabilistic prediction effects are reflected across several stages of language processing.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that activation of the FFG remained significant during phonological and semantic processing after the subtraction of activation during font-size judgment. This implies that the mid-fusiform area is involved in the finer visuo-orthographic analysis of characters and not the recognition of the general outline of characters, and may be responsible for the integration of visual, phonological and semantic information (Qin et al, 2021).…”
Section: Orthographic Processingmentioning
confidence: 99%